Financial development and inequality: The role of religious freedom - Benard Ohene Kwatia; Godfred Amewu; Christopher Boachie (Modern Finance, 2025)
The study investigates whether religious freedom affects the relationship between financial development and income inequality in sub-Saharan Africa. The study employs panel data analysis and a causal, quantitative research approach to achieve its research goals, focusing on 39 sub-Saharan African nations between 2000 and 2020. Based on the availability of data, this time frame was selected. Using the instrumental variable estimation method, the study reveals a significant positive correlation between financial development and income inequality, while religious freedom negatively influences income inequality. Again, the moderation analysis shows that religious freedom tends to amplify the inequality-widening effect of financial development. This finding indicates that while religious freedom is beneficial, it should be complemented with policies that ensure financial development does not exacerbate inequality. Governments and religious institutions can collaborate to promote financial literacy, equitable tax policies, and wealth redistribution mechanisms such as progressive taxation and social welfare programs.